Post Marketing Surveillance Study to evaluate the Efficacy and Safety for the Combination of Alpha Lipoic Acid, Gingko Biloba, Vitamin C, Zinc, Magnesium, Vitamin B6, Methylcobalamin, Vitamin E and Chromium Picolinate in the Patients of Tinnitus - Kiran, Dr. Mayuresh; Pawaskar, Mr. Lalit; Waghambare, Ms. Pramita; Sheikh, Ms. Shaheen (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Tinnitus is the false perception of sound. Normally it is considered to be developed due to oxidative stress to the inner ear. This study was conducted to test the efficacy and safety for the combination of Alpha lipoic acid, Gingko biloba, Vitamin C, Zinc, Magnesium, Vitamin B6, Methylcobalamin, Vitamin E and Chromium Picolinate in the patients of tinnitus. Method: The study was conducted on 165 patients out of which 142 completed the study. Efficacy was evaluated by tinnitus symptom score (TSS). Patients were asked to rate the TSS ranging from 0 to 10 where 0 means no symptom and 10 means maximum tolerable symptoms. Safety assessment was made by analysing the adverse events reported by the patient. Efficacy and safety evaluation was done on day 0, 10 and 22. Results: Patients had TSS 6.26 on baseline visit which was reduced to 4.50 at day 10 and was further reduced to 2.47 at day 22. Also, in the clinical trial duration of 22 days, only 5 episodes of the adverse drug reactions were reported by the patient and all of them were of non-serious in nature and mild in intensity. Conclusion: The fixed dose combination of Alpha lipoic acid 200 mg, Gingko biloba 120 mg, Vitamin C 30 mg, Zinc 12 mg, Magnesium 10 mg, Vitamin B6 3 mg, Methylcobalamin 1500 mcg, Vitamin E 10 IU and Chromium Picolinate 1.66 mg equivalent to elemental chromium 200 mcg was found to be efficacious and safe for the treatment of Tinnitus.